(untitled) (The Pakistan Development Review, 2005)
A number of developing countries from Asia, Latin America and Eastern Europe have experienced surge in capital inflows during recent years.1 These inflows have potential effects on macroeconomic stability; export competitiveness, and inflation. If not properly managed, these inflows can induce appreciation of local currency leading to serious repercussions for the rest of the economy. Under these conditions, the proactive role of monetary authorities in the management of capital inflows was highly desirable, wherein they intervened in the domestic exchange market in order to contain volatility in exchange rate besides accumulation of foreign exchange reserves. The main instruments available to deal with the possible effects of large capital inflows include sterilised intervention, fiscal tightening, trade and exchange liberalisation including easing controls on capital outflows. The foreign exchange interventions are typically accompanied by active sterilisation policy to keep inflation under control.